Genome-Wide Analysis and Heavy Metal-Induced Expression Profiling of the HMA Gene Family in Populus trichocarpa - Li, Dandan; Xu, Xuemei; Hu, Xiaoqing; Liu, Quangang; Wang, Zhanchao; Zhang, Haizhen; Wang, Han; Wei, Ming; Wang, Hanzeng; Liu, Haimei; Li, Chenghao (Frontiers in Plant Science, 2015)
The heavy metal ATPase (HMA) family plays an important role in transition metal transport in plants. However, this gene family has not been extensively studied in Populus trichocarpa. We identified 17 HMA genes in P. trichocarpa (PtHMAs), of which PtHMA1–PtHMA4 belonged to the zinc (Zn)/cobalt (Co)/cadmium (Cd)/lead (Pb) subgroup, and PtHMA5–PtHMA8 were members of the copper (Cu)/silver (Ag) subgroup. Most of the genes were localized to chromosomes I and III. Gene structure, gene chromosomal location, and synteny analyses of PtHMAs indicated that tandem and segmental duplications likely contributed to the expansion and evolution of the PtHMAs. Most of the HMA genes contained abiotic stress-related cis-elements. Tissue-specific expression of PtHMA genes showed that PtHMA1 and PtHMA4 had relatively high expression levels in the leaves, whereas Cu/Ag subgroup (PtHMA5.1- PtHMA8) genes were upregulated in the roots. High concentrations of Cu, Ag, Zn, Cd, Co, Pb and Mn differentially regulated the expression of PtHMAs in various tissues. The preliminary results of the present study generated basic information on the HMA family of Populus that may serve as foundation for future functional studies.